Susceptibility evaluation and PK/PD integration of tulathromycin against Actinobacillus pleuropneumoniae during the mutant selection window - Wang, Hongjuan; Zhang, Longfei (Frontiers in Veterinary Science, 2024)
Introduction Actinobacillus pleuropneumoniae (APP) is a serious pathogen that affects the development of livestock breeding. Due to excessive use of antimicrobial drugs, many multidrug-resistant bacteria have emerged and spread, which have threatened the livestock industry. Therefore, we established a peristaltic pump infection model (PPIM) to evaluate the susceptibility change and pharmacokinetic/pharmacodynamic (PK/PD) integration of tulathromycin against APP during the mutant selection window (MSW) for preventing the emergence of mutant-resistant bacteria. Methods The 99% minimum inhibitory concentration (MIC99) and mutant prevention concentration (MPC) of tulathromycin against APP were measured using the agar-plate method. After the model of dynamic infection had been established based on tulathromycin data in lungs, different dosages were administered to make the drug concentrations located in different parts of the MSW. The population and sensitivity of APP were monitored. Tulathromycin concentrations were measured by high-performance liquid chromatography-tandem mass spectrometry. Finally, a sigmoid Emax model was used to analyze the relationships between PK/PD parameters and antibacterial effects. Results and discussion The values of MIC, MIC99, and MPC of tulathromycin against APP were 2, 1.4, and 44.8 μg/mL, respectively. The PPIM was stable. An elimination effect without regrowth was observed at 5.6 to 44.8 μg/mL (−4.48 to −7.05 Log10 CFU/mL, respectively). The MIC of APP increased 32-fold at 8 MIC99. AUC168 h/MIC99 had the best fit with the antibacterial effect (R2 = 0.9867). The AUC168 h/MIC99 required to achieve bacteriostatic, bactericidal, and clearance effects were 1.80, 87.42, and 198 h, respectively. Our results could provide guidance for the clinical application of tulathromycin to treat APP infection and avoid the generation of drug-resistant bacteria.